Engagement and Happiness levels in Lima’s working college students - Davey Contreras, Katherine Abigail (2017)
This paper is meant to study if there is a relation between happiness and engagement in graduate students who work at the same time. To do this, a descriptive correlational study that features a cross-sectional design was carried out. 338 students from private institutions were evaluated (Universities and colleges).The data were obtained using the Happiness scale of Lima, with a criterion validity of the scale of positive affect of r=.48, p 0.80 and reliability of α>.77. The Happines scale has the following factors: absence of deep suffering, personal fulfillment, life satisfaction, , ´joie de vivre´, while the Engagement questionnaire takes into account the components of vigor, dedication and absorption. Statistically significant correlations between happiness and Engagement were found in students working. The happiness variable had the highest correlation with the components of Engagement: dedication and then with vigor. The factors of profound suffering absence and life satisfaction that belongs to the happiness variable correlate significantly with the components of Engagement: dedication and vigor.